Regulating microstructure, mechanical properties and corrosion resistance of laser direct energy deposited Al0.5Mn0.5CoCrFeNi high-entropy alloy by annealing heat treatment - Zhaoyang Liu; Tiannan Mai; Jiawei Liu; Tao Zou (Virtual and Physical Prototyping)
A novel Al0.5Mn0.5CoCrFeNi high-entropy alloy (HEA) was additively manufactured by laser direct energy deposition (LDED) process and annealed at 900 ℃. The microstructure, mechanical properties and corrosion resistance of the prepared HEA were investigated and regulated by annealing time. The as-deposited microstructure is made up of well-developed columnar dendrites featured by face-centered cubic phase (FCC) and mature interdendritic regions co-structured by body-centered cubic (BCC) and Cr-Fe-rich σ duplex phases. The annealing heat treatment noteworthily enhances the hardness and improves the ultimate tensile strength with a deterioration of toughness by facilitating the precipitation of nanoscale B2 phases within the FCC matrix and the coarsening of σ phases at interdendritic regions, successfully regulating the mechanical performance between high-ductility (670.0 MPa, 25.3%) and high-strength (1015.6 MPa, 5.9%). The corrosion resistance is significantly improved by 2-hour annealing, and then deteriorates due to the severe passive film destruction of the FCC matrix by gradually coarsened B2 nanoparticles and the stability and compactness reduction of passive films by the coarsening of σ phases and formation of high-valence metal cations. These results contribute to exploring and regulating novel high-performance HEAs by the LDED process and annealing heat treatment.